Social policy review. - Jolly, Andy; Cefalo, Ruggero; Pomati, Marco (Social Policy Review., 2022)
Experts review the leading social policy scholarship from the past year in this comprehensive volume. Published in association with the Social Policy Association, this volume addresses current issues and critical debates throughout the international social policy field.